EL SIMULADOR: LA PERCEPCIÃ“N DE LOS ESTUDIANTES DE LA LICENCIATURA EN RELACIONES COMERCIALES EN LA UTILIZACIÃ“N DEL SIMULADOR DE LA PLATAFORMA A DISTANCIA - Ramos, Cristhell Abigail DÃaz; Ãlvarez, Aida Dinorah GarcÃa; Calacich, Salvador Neme (European Scientific Journal, ESJ, 2015)
Education is an activity able of adapting to changing human needs. Education is and will remain as one of the tools to achieve goals and objectives. Educational changes have allowed the development of TICs named, and in turn, have allowed the entrance of a new model named systems of knowledge generation, promoting education to continue being valid. This is rooted in the need for new technological innovations that flow constantly and the way students can access these tools to develop themselves in their professional field. Based on the above approach, surveys were employed and show results reflect that students are willing to interact with simulators that allow them to their develop academically and professionally, with the goal of getting prepared for workplace.